Clinical Comparison of Autogenous Bone Graft with and without Plasma Rich in Growth Factors in the Treatment of Grade II Furcation Involvement of Mandibular Molars - Ardeshir Lafzi; Adileh Shirmohammadi; Masoumeh Faramarzi; Sahar Jabali; Arman Shayan (Tabriz University of Medical Sciences, 2013)
Background and aims. Plasma rich in growth factors (PRGF) is a concentrated suspension of growth factors, which is used to promote periodontal tissue regeneration. The aim of this randomized, controlled, clinical trial was to evaluate of the treatment of grade II mandibular molar furcation involvement using autogenous bone graft with and without PRGF. Materials and methods. In this double-blind clinical trial, thirty mandibular molars with grade II furcation involvement in 30 patients were selected. The test group received bone graft combined with PRGF, while the control group was treated with bone graft only. Clinical parameters included clinical probing depth (CPD), vertical clinical attachment level (V-CAL), horizontal clinical attachment level (H-CAL), location of gingival margin (LGM), surgically exposed horizontal probing depth of bony defect (E-HPD), vertical depth of bone crest (V-DBC), vertical depth of the base of bony defect (V-DBD), and length of the intrabony defect (LID). After six months, a re-entry surgery was performed. Data were analyzed by SPSS 14, using Kolmogorov, Mann-Whitney U, and paired t-test. Results. After 6 months, both treatment methods led to significant improvement in V-CAL and H-CAL and significant decreases in CPD, E-HPD, V-DBD and LID; there was no significant difference in LGM and V-DBC in any of the treated groups compared to the baseline values. Also, none of the parameters showed significant differences between the study groups. Conclusion. Although autogenous bone grafts, with or without PRGF, were successful in treating grade II furcation involvement, no differences between the study groups were observed.